2015
DOI: 10.1002/ente.201402155
|View full text |Cite
|
Sign up to set email alerts
|

Gravure‐Printed ZnO in Fully Roll‐to‐Roll Printed Inverted Organic Solar Cells: Optimization of Adhesion and Performance

Abstract: We present a gravure printing process for zinc oxide (ZnO) nanoparticle ink to be used as a hole‐blocking layer in inverted organic solar cells, enabling the production of patterned devices with freedom of design. The printability of the ink is optimized in a pilot‐scale roll‐to‐roll (R2R) process, leading to smooth layers having a thickness of few tens of nanometers. The properties of the printed ZnO film are further optimized using R2R post‐printing plasma treatment, which leads to increased adhesion and pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Based on the paper published by Vilkman et al, the properties of the printed ZnO film can be optimized using R2R post‐printing plasma treatment that leads to increased adhesion and PCE . For this reason, another batch of ICBA modules were prepared in R2R process where the same post‐printing plasma treatment phase for ZnO layer was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the paper published by Vilkman et al, the properties of the printed ZnO film can be optimized using R2R post‐printing plasma treatment that leads to increased adhesion and PCE . For this reason, another batch of ICBA modules were prepared in R2R process where the same post‐printing plasma treatment phase for ZnO layer was applied.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO was gravure printed with the printing speed of 8 m min −1 . The R2R plasma process was performed with a web speed of 2 m min −1 and, an argon–nitrogen mixture with the power of 200 W . Photoactive layer of P3HT:ICBA and P3HT:[60]PCBM were gravure printed with the printing speed of 8 m min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Metal oxides. (a) FTIR (Fourier transform infrared spectroscopy) spectra of commercial titania nanoparticles inkjet‐printed and plasma treated between 0 (black) and 64 s (red; left) exhibiting a decrease in carbon groups and corresponding chronoamperometric measurements with a period of 10 s confirming increased film conductivity, reprinted with permission from Homola et al [ 123 ] (b) Schematic and photos of a roll‐to‐roll (R2R) process for ZnO‐based organic photovoltaic devices consisting of rotary screen and gravure printing steps reprinted with permission from Vilkman et al [ 124 ] The gravure printed ZnO films were post‐print plasma treated to increase adhesion and power conversion efficiency…”
Section: Schemesmentioning
confidence: 99%
“…It has also been reported that ZnO electrodes benefit by plasma processing. [ 124 ] Commercially‐available ZnO nanoparticle suspensions were gravure printed on ITO‐coated PET substrates using a large‐scale R2R printing machine (Figure 10b). After printing, the structures were exposed to a 200 W atmospheric pressure plasma formed in a mixture of Ar and O 2 .…”
Section: Schemesmentioning
confidence: 99%
“…ZnO is a well‐known n‐type semiconductor with high electron mobility and transmittance . In particular, its low‐temperature solution‐processability (<150 °C) is appropriate for roll‐to‐roll printing technology on flexible substrates . However, its relatively high work function of ≈4.3 eV requires further electric dipole layers for improving the charge transporting characteristics of the CQD layers .…”
Section: Introductionmentioning
confidence: 99%